Data Mining : know it all - Chakrabarti, Soumen., et al, Cox, Earl (Morgan Kaufmann, 2008)
Data Mining : Know It All expertly combines the finest data mining material from the Morgan Kaufmann portfolio with individual chapters contributed by aselect group authors